Hubungan Tingkat Pengetahuan Hand Hygiene Five Moment Dengan Kepatuhan Pelaksanaannya Di Puskesmas Sukajadi Kabupaten Bandung - Amaliah, Rela; Heriyanto, Yonan; Fatimah, Siti; Praptiwi, Yenni Hendriani (Poltekkes Kemenkes Bandung, 2024)
Background: Efforts to prevent and break the chain of transmission of infectious diseases should be carried out simultaneously. IPC principles and procedures must be adhered to when doing so. One of the principles is hand hygiene. All health workers must understand the five steps for proper hand hygiene, as this will prevent contamination through body fluids, blood, secretions, excretions and non-intact skin. Objective: The aim of this research is to determine whether there is a relationship between the level of knowledge and compliance of health workers at Sukajadi Community Health Center, Bandung Regency with hand hygiene practices. Method: This is a type of analytical research that uses a cross-sectional approach. A total of 26 medical personnel working at the Sukajadi Community Health Center used total sampling techniques. To collect data, questionnaires and observation sheets were used. The data used for analysis was tested using the Kendall Tau test. Results: The results of the study showed that most of the health workers at the Sukajadi Community Health Center had good knowledge about implementing hand hygiene (84.6%), but a small portion did not do it (15.4%). Conclusion: The results of statistical tests on research data show that there is a significant relationship between the level of five moment hand hygiene knowledge of health workers and compliance with its implementation at the Sukajadi Health Center, Bandung Regency.